2011
DOI: 10.1111/j.1468-3083.2011.04055.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in melanoma patients with negative sentinel lymph node: does false‐negative specimens entirely account for this phenomenon?

Abstract: Even if SLN status remains the most important prognostic factor for melanoma patients, progressive disease after a negative SLNB is a relatively frequent event. However, in our opinion, only a part of negative SLNB patients with metastatic spreading should be considered as false negative (7.75%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 30 publications
4
39
2
Order By: Relevance
“…In our study, the false negative rate (10/54 = 18.5%) was also similar to the rate calculated in other studies (5.7% to 21%) [14]. Beyond the technical problems associated with the SLN procedure, false negatives may be related to different factors: the time it takes to learn to perform the technique [19], lymphatic drainage disruption related to primary tumour excision, lymphatic obstruction by tumor cell embolism, the presence of a neck SLN [7], inadequate histological analysis and hematogenous dissemination.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study, the false negative rate (10/54 = 18.5%) was also similar to the rate calculated in other studies (5.7% to 21%) [14]. Beyond the technical problems associated with the SLN procedure, false negatives may be related to different factors: the time it takes to learn to perform the technique [19], lymphatic drainage disruption related to primary tumour excision, lymphatic obstruction by tumor cell embolism, the presence of a neck SLN [7], inadequate histological analysis and hematogenous dissemination.…”
Section: Discussionsupporting
confidence: 80%
“…Only patients with a primary cutaneous melanoma (tumour thickness > 1 mm) and without clinical evidence of metastasis who underwent SLNB between January 2002 and December 2009 were included. Furthermore, patients with head and neck CM were also excluded because of the complexity of lymphatic drainage, multi-site drainage and the high number of false negatives [6,7]. Since this retrospective study was conducted in France, it was not eligible for submission to our research ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…Melanoma of the head and neck was observed to recur within the shortest time interval (9.5-19 months following SLNBx) [10,12]. Risk factors associated with recurrence of melanoma following a negative SLNBx included increased depth of the primary lesion, the presence of ulceration, advanced age at diagnosis and location of the primary lesion on the head and neck [13,14]. Distant disease was the most common site of recurrence, representing 31.3-70.0% of all patients who developed recurrent disease following a negative SLNBx (mean: 46.2%) ( Table 2).…”
Section: Recurrence After Negative Slnbxmentioning
confidence: 98%
“…Current studies have identified phenotypic factors such as increased tumor thickness [7,[13][14]18,[26][27][28][29][30], presence of ulceration [7,[13][14][26][27][29][30][31][32], increased number of mitoses [26,29,31] and increased patient age [13][14]18,27] as risk factors for tumor recurrence. Attempts to further identify high-risk melanoma patients using molecular studies for melanoma markers such as in situ PCR and RT-PCR for MART1, MAGE-3, GalNAc-T and PAX3 mRNA have had some success, but suffer from the challenges of both broadly deploying complex technology as well SyStematic Review Hodges, Jones, Jones et al…”
Section: Melanoma Biology and Recurrencementioning
confidence: 98%
“…We are still awaiting the results of the Multicenter Selective Lymphadenectomy Trial II (MSLT-II) in which patients with a positive sentinel node are randomized to completion lymphadenectomy or observation with ultrasound. Despite the risk of a false-negative sentinel lymph node [38], its role in predicting survival is still high enough to justify the procedure. Patients need to be well informed about the prognostic value of this procedure but access to adjuvant treatment for stage III melanoma may also justify the use of this procedure in the future.…”
Section: What Is New In the Treatment Of Cutaneous Melanoma?mentioning
confidence: 99%